STUDI KEKUATAN BATULEMPUNG DENGAN UJI SCHMIDT HAMMER DAN UNIAXIAL COMPRESSIVE STRENGTH FORMASI BALIKPAPAN DAN PULAUBALANG SAMARINDA, KALIMANTAN TIMUR: STUDY OF CLAYSTONE STRENGTH USING THE SCHMIDT HAMMER TEST AND UNIAXIAL COMPRESSIVE STRENGTH BALIKPAPAN AND PULAUBALANG FORMATIONS IN SAMARINDA, EAST KALIMANTAN - Silalahi, Abdi Brema; Trides, Tommy; Nugroho, Windhu; Oktaviani, Revia; Juvensius Pontusi, Albertus (JURUSAN TEKNIK PERTAMBANGAN UPR, 2023)
The Schmidt hammer has been used worldwide as a rapid index test to determine rock strength and deformability characterization, this is because it is easy to use, low cost and can be performed in a short time and is non-destructive to samples. There are 6 sampling locations, where the first location was carried out on the outcrop of Jln. Kadrie Oening, the second location was carried out on the outcrop of Jln. Ringroad I, the third location is carried out on the outcrop of Jln. Ringroad II, the fourth location is done on the outcrop of Jln. Hj. Mastuang, the fifth location is done on the outcrop of Jln. Padat Karya, the sixth location is carried out on the outcrop of Jln. Mount Lingai City of Samarinda, East Kalimantan. Research uses quantitative methods, activity plans by making a framework or flowchart. There are many published papers that focus on getting a correlation between Schmidt hammer and unconfined compressive strength. The compressive strength value produced in the Pulaubalang Formation is greater than the compressive strength value in the Balikpapan Formation, where the compressive strength value in the Pulaubalang Formation is 1.187 MPa-1.445 MPa, while the compressive strength value in the Balikpapan Formation is 0.774 MPa-1.032 MPa. The reflected value in the Pulaubalang Formation is greater than the reflected value in the Balikpapan Formation, where the reflected value in the Pulaubalang Formation is 11.167-11.875, while the reflected value in the Balikpapan Formation is 10.417-10.708. There is a positive linear correlation between the compressive strength and the reflected value, where the higher the compressive strength, the higher the rebound value. Keywords: Compressive Strength Value, Rebound Number